On the occasion of the 45th anniversary of the death of the academician Jovan Hadži (1884-1972): Studies in arachnology by Jovan Hadži, a critical review - Dimitrijević, Rajko N. (Archives of Biological Sciences, 2017)
The scientific activities of Jovan Hadži, a member of the Serbian, Slovenian and Czechoslovakian Academies of Sciences and Arts, spread over more than six decades (1906-1972), and covered fields such as evolutionary morphology, evolutionary systematics, arachnology, ontogeny, biogeography, paleontology and the ecology of various groups of animals (marine, fresh water and land). Jovan Hadži’s scientific opus includes over 900 scientific studies, monographs, books and publications in foreign and domestic scientific journals. In addition to his scientific work, Jovan Hadži paid special attention to the popularization of biology and biological thinking in numerous popular and scientific articles, lectures and textbooks.